ENGLISH – VIETNAMESE TRANSLATION OF IDIOMS AND PROVERBS RELATING TO ANIMALS IN CULTURAL DOMAIN = Dịch thành ngữ, tục ngữ về loài vật từ tiếng Anh sang tiếng Việt trên khía cạnh văn hóa - Phí, Hải Yến (2020)
It cannot be denied that language and culture have a mutual interaction and close connection with each other. The characteristics of a culture is presented via a language, and vice versa, a language is also a vital component of a culture, especially in the globalized world in which cross-cultural and bilingual issues become popular and the translation becomes necessary. There exists the culture-bounded terms which are, as a result, playing an important part in translation studies. If the culture-related issues in translation are solved, the gap of cultural differences between countries, such as Vietnam and the English-speaking world, would be shortened. Among such culture-bound terms, proverbs and idioms have been considered the most attributive factor of language in a culture. In addition, animal connotations play significant roles. This study aims at reckoning the similarities and differences of the animal connotations in the proverbs, idioms between the Vietnamese culture and Englishspeaking countries’ cultures. A further goal of the research is to figure out the most appropriate procedures applied in translating such culture-bounded terms. Fulfilling the goals of the study, there are three main steps that the researcher followed: first, cultural correspondence of each proverb and idiom between the two cultures was defined, second, the strategies applied in translating the proverbs and idioms were examined, and finally the similarities and differences between the two cultures were shown for the better understanding of the translation of cultural terms. From the results of the study, there would be a close look at not only the translation of proverbs and idioms but also the similar and different concepts of the two cultures. That would be a helpful reference for next generations of researchers in both fields of translation and culture.